LAPOROSCOPIC SLEEVE GASTRECTOMY. ROLE AND PLACE IN BARIATRIC SURGERY - M. B. Fishman; V. M. Sedov; V. Yan (Вестник хирургии имени И.И. Грекова, 2016)
Laparoscopic sleeve gastrectomy (LSG) was performed in 522 patients at the period from 2007 to 2015. The operation was carried out by different methods. It was stated that «the ideal candidates» for choosing LSG operation were the patients without metabolic syndrome (MS) and body-weight index, which wasn’t higher than 48 kg/m². The operation could be performed on patients younger than 40 years old in order to correct disorders of insulinic and cholesterol metabolism. Patients with MS have limitations for LSG application, because of this reason, the operation is advisable for younger age group without severe accompanying pathology. The operation could be applied in older age group in order to stabilize general condition in case of high risks as the first (sometimes the last) stage of treatment for the patients whom more effective operation couldn’t be recommended.